2017
DOI: 10.1002/bit.26247
|View full text |Cite
|
Sign up to set email alerts
|

Human pathogens in plant biofilms: Formation, physiology, and detection

Abstract: Fresh produce, viewed as an essential part of a healthy life style is usually consumed in the form of raw or minimally processed fruits and vegetables, and is a potentially important source of food-borne human pathogenic bacteria and viruses. These are passed on to the consumer since the bacteria can form biofilms or otherwise populate plant tissues, thereby using plants as vectors to infect animal hosts. The life cycle of the bacteria in plants differs from those in animals or humans and results in altered ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 131 publications
(217 reference statements)
3
25
0
1
Order By: Relevance
“…To overcome this challenge, large volumes of food samples can be filtered and concentrated to small volumes, reducing time for sample preparation. As we have previously shown, this increases the total cell concentration in the retentate …”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…To overcome this challenge, large volumes of food samples can be filtered and concentrated to small volumes, reducing time for sample preparation. As we have previously shown, this increases the total cell concentration in the retentate …”
Section: Introductionsupporting
confidence: 61%
“…These filter modules were integrated into a four‐channel multiplexed system, referred to as Continuous Cell Concentration Device (C3D), allowing more samples to be processed simultaneously (Figure ). The operation of the C3D is based on use of multiplexed peristaltic pumps that control sample flow on the retentate side of the membrane and sweep flow on the permeate side (Figure ) as described by Zuponcic et al Operation is analogous to previously reported single‐channel configurations of this hollow fiber system …”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Following prefiltration, Salmonella cells in ground turkey samples were originally present at about 1–20 CFU/mL. These were concentrated and recovered using the sequence of Figure and the hollow fiber microfiltration process previously developed …”
Section: Resultsmentioning
confidence: 99%